[Date Index]
[Thread Index]
[Author Index]
Re: fullsimplify problem
*To*: mathgroup at smc.vnet.net
*Subject*: [mg52923] Re: [mg52908] fullsimplify problem
*From*: Andrzej Kozlowski <akoz at mimuw.edu.pl>
*Date*: Fri, 17 Dec 2004 05:18:33 -0500 (EST)
*Sender*: owner-wri-mathgroup at wolfram.com
What do you mean by " incorrect"? It's correct and it's primary school
maths.
( - a / b^2) = = ( + a / b^2) -> (2 a / b^2)==0 -> (a/b)*(2/b)==0 ->
(a/b)==0.
????????
Andrzej Kozlowski
On 16 Dec 2004, at 17:41, symbio wrote:
> Given ( - a / b^2) = = ( + a / b^2), it can be written as (-2 a /
> b^2), but
> when I use FullSimplify on that equation, I get the incorrect result (
> a /
> b ) = = 0. How is this possible?
>
> In[2]:=
> -a/b^2 == a/b^2
> % // FullSimplify
> Out[2]=
> \!\(\(-\(a\/b\^2\)\) == a\/b\^2\)
> Out[3]=
> \!\(a\/b == 0\)
>
> In[5]:=
> -2a/b^2 == 0 // FullSimplify
> Out[5]=
> \!\(a\/b == 0\)
>
Prev by Date:
**Re: please solve**
Next by Date:
**Re: please solve**
Previous by thread:
**Re: fullsimplify problem**
Next by thread:
**Re: fullsimplify problem**
| |